2017
DOI: 10.1007/s12035-017-0618-z
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 (TLR4) and Triggering Receptor Expressed on Myeloid Cells-2 (TREM-2) Activation Balance Astrocyte Polarization into a Proinflammatory Phenotype

Abstract: Astrocytes react to brain injury with a generic response known as reactive gliosis, which involves activation of multiple intracellular pathways including several that may be beneficial for neuronal survival. However, by unknown mechanisms, reactive astrocytes can polarize into a proinflammatory phenotype that induces neurodegeneration. In order to study reactive gliosis and astroglial polarization into a proinflammatory phenotype, we used cortical devascularization-induced brain ischemia in Wistar rats and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 51 publications
0
81
0
1
Order By: Relevance
“…TLR4 and MMP9 are the important mediators in inflammation-induced BSCB breakdown [5,15,28]. TLR4 elevation induces astrocytes polarization [24]. The reactive astrocytes around microvessels activate endothelial MMP9 [25] or release inflammatory mediators such as cytokines IL-1β, IL-6, and TNFα to regulate blood-brain barrier permeability in inflammation [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR4 and MMP9 are the important mediators in inflammation-induced BSCB breakdown [5,15,28]. TLR4 elevation induces astrocytes polarization [24]. The reactive astrocytes around microvessels activate endothelial MMP9 [25] or release inflammatory mediators such as cytokines IL-1β, IL-6, and TNFα to regulate blood-brain barrier permeability in inflammation [42].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported that toll-like receptors 4 (TLR4) are strongly associated with the inflammatory responses after I/R injury and mediate the motor dysfunction and BSCB disruption [7,15,23]. It has also been reported that brain ischemia induces TLR4 expressions in astrocytes, and that TLR4 activation leads to an astroglial polarization towards an inflammatory phenotype [24]. Astrocytes contribute to blood-brain barrier damage through activation of endothelial matrix metalloproteinase 9 (MMP9) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that Triggering Receptor Expressed on Myeloid cells 2, also known as (TREM2), is an efficient negative regulator of TLR-4 signaling [145][146][147]. TREM2 is a membrane receptor that mediates critical functions of microglia, such as suppression of pro-inflammatory cytokines and promotion of phagocytosis of apoptotic neurons and cell debris [148].…”
Section: Cur and Tlr-4 In Neuroinflammatory Diseasesmentioning
confidence: 99%
“…ese studies thereby suggest that TLR4 protein is not expressed in detectable amounts, using immunohistochemistry, under basal conditions in normal tissue. However, during injury, there appears to be at least a small amount of TLR4 able to initiate ligand binding of various danger-associated molecular patterns (DAMPs) and subsequent signal amplification [10,30]. However, we did observe baseline TLR4 message levels in our cultured astrocyte cell line stimulated with PBS; Figure 5(a).…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have shown TLR4 expression in penumbral astrocytes during acute focal cerebral ischemia [5]. More recent studies also show that TLR4 is also expressed by penumbral astrocytes in a model of cortical devascularization [10]. However, it is not known whether TLR4 signaling occurs in these astrocytes during both the acute and chronic phases of focal cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%